THE EFFECT OF HUMAN RESOURCE COMPETENCE AND ORGANIZATIONAL CULTURE ON THE QUALITY OF SERVICES IN BATUDAA PUSKESMAS GORONTALO DISTRICT - mohamad, andriani; Ibrahim, Meimoon; Olii, Rahmat (LP2M Universitas Bina Mandiri Gorontalo, 2024)
The purposes of this study are: 1) To determine and analyze the partial effect of HR competence on service quality at Batudaa Health Center, Gorontalo Regency; 2) To find out and partially analyze the influence of organizational culture on service quality at Batudaa Health Center, Gorontalo Regency; 3) To determine and analyze the simultaneous influence of HR competence and organizational culture on service quality at Batudaa Health Center, Gorontalo Regency. This research is a quantitative descriptive approach Research results: 1) Human resource competence has a partial effect on service quality with a contribution of 63.4% influence. Thus, the hypothesis in this study assumes that the competence of human resources has a partial effect on service quality and has been proven and can be accepted; 2) Organizational Culture has a partial effect on Service Quality with an influence contribution of 26.6%. Thus, the hypothesis in this study suggests that organizational culture has a partial effect on service quality and has been proven and can be accepted; 3) Human Resource Competence and Organizational Culture simultaneously have a simultaneous effect on Service Quality with an influence contribution of 72.20%. Thus the hypothesis in this study assumes that the competence of HR and Organizational Culture simultaneously has a simultaneous effect on Service Quality has been proven and can be accepted.